2000
DOI: 10.1074/jbc.m909835199
|View full text |Cite
|
Sign up to set email alerts
|

Structural Model of the Fe-Hydrogenase/Cytochromec 553 Complex Combining Transverse Relaxation-optimized Spectroscopy Experiments and Soft Docking Calculations

Abstract: Fe-hydrogenase is a 54-kDa iron-sulfur enzyme essential for hydrogen cycling in sulfate-reducing bacteria. The x-ray structure of Desulfovibrio desulfuricans Fehydrogenase has recently been solved, but structural information on the recognition of its redox partners is essential to understand the structure-function relationships of the enzyme. In the present work, we have obtained a structural model of the complex of Fe-hydrogenase with its redox partner, the cytochrome c 553 , combining docking calculations an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 29 publications
3
42
0
Order By: Relevance
“…The lysine distribution on the surface of Cc 553 , in conjunction with studies of ionic strength dependence for complex formation, suggests that electrostatic interactions play an important role in the formation of the complexes between the cytochrome and FDH (SebbanKreuzer et al, 1998b) or FeHase (Morelli et al, 2000a). The solution structure of DvH Cc 553 is available Blackledge et al, 1995;PDB entry 1dvh) and was used in the docking studies reported hereafter.…”
Section: Cytochrome C 553 Complexes With Ferredoxin I and [Fe]-hydrogmentioning
confidence: 98%
“…The lysine distribution on the surface of Cc 553 , in conjunction with studies of ionic strength dependence for complex formation, suggests that electrostatic interactions play an important role in the formation of the complexes between the cytochrome and FDH (SebbanKreuzer et al, 1998b) or FeHase (Morelli et al, 2000a). The solution structure of DvH Cc 553 is available Blackledge et al, 1995;PDB entry 1dvh) and was used in the docking studies reported hereafter.…”
Section: Cytochrome C 553 Complexes With Ferredoxin I and [Fe]-hydrogmentioning
confidence: 98%
“…A recently developed computer program [21] allowed us to use the NMR data to provide a model of the interaction. In a similar approach, heteronuclear NMR and docking calculations were used for building structural models of the cytochrome c 553 -ferredoxin complex and a combination of TROSY experiments and docking calculations were used for the study of the [Fe]-hydrogenase-cytochrome c 553 complex [22,23]. Other, more recent, applications of similar strategies include the cytochrome b 5 -myoglobin [24] and the cytochrome ccytochrome f [25] complexes.…”
Section: Introductionmentioning
confidence: 99%
“…4). The propionate rotation has been observed in others proteins, such as cytochromes and haloperoxidases [47][48][49][50]. In the crystal structure of dehaloperoxidase of Amphitrite ornata (pdb code 3DR9) there are water molecules at hydrogen bond distance (2.2-2.9Å) next to the switched A ring propionate group.…”
Section: Discussionmentioning
confidence: 93%